Islamic Economics in the Interpretation of the Qur'an - Mohammad Elwim Cahyadi Dzakwan (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2025)
The Quran is a book of guidelines for Muslims. The Quran and As-Sunnah as sources of Islamic law are the clues of mankind, one of which is in the field of economics. These two sources of law serve as guidelines for mankind not to get lost. The economic development of Islam is also inseparable from the Quran and the As-Sunnah. In making this journal, the method of literature review and literature review is used. The data collection technique carried out is to collect data from various library sources, namely from books, journals, articles and also seminar results. This journal will discuss basic knowledge about economics, namely the meaning of Islamic Economics, the principles of Islamic Economics and the basic values of Islamic Economics